KONSEP DAN PERSEPSI MASYARAKAT ETNIS MEYAH TENTANG HUTAN ADAT DI KAMPUNG MEREJEMEG, KABUPATEN MANOKWARI - Yohanes Yoseph Rahawarin; Adolof Wam; Kristian Imburi; Reinardus Liborius Cabuy; Alexander Rumatora (Jurnal Belantara, 2021)
The study was aimed to obtain the concept of indigenous forest according to the Meyah ethnic community, the Meyah ethnic community's perception of indigenous forest, and the factors that influence the use of the indigenous forest by the Meyah ethnic community. Descriptive methods with observation and interview techniques are used in this study. Respondents were selected by purposive sampling, as many as 30 families. The results show that the concept of indigenous forest according to the Meyah ethnic community is a forest area given by God the Creator of the Universe as human property rights to live for generations, reproduce and adapt to their environment, and utilize the resources in the forest. Ownership of indigenous forests is controlled by individuals or clan groups for generations in certain areas marked by natural boundaries. The first activity in utilizing the forest as a source of life was by clearing land for houses and gardening as well as collecting forest products, which were used as the basis for determining the boundaries of land and forest rights. The Meyah ethnic community has a strong perception of indigenous forests, both perceptions of indigenous forest ownership, indigenous forest sustainability, and indigenous forest use. The factors that influence the Meyah ethnic community in the use of indigenous forests consist of a) determining factors, namely: customs and way of life about the forest; b) supporting factors, namely: livelihood and length of stay, and c) driving factors, namely: the role of traditional and religious leaders.